Institutional thinking: A new settlement between public and private. Issue 4 (March 2014) - Painter, Anthony
<x xml:space="preserve">Abstract</x> Mediated conversation is a lost art, argues Anthony Painter, and to fill this gap in our democracy he proposes a bold new vision of the institution, defined by its purpose to negotiate between public and private interests through rules and inclusivity.